Primarily hip-borne load carriage does not alter biomechanical risk factors for overuse injuries in soldiers. Issue 2 (February 2019) - Lenton, Gavin K.; Saxby, David J.; Lloyd, David G.; Billing, Daniel; Higgs, Jeremy; Doyle, Tim L.A.
Abstract: Objectives: To determine the effects of different body armour types, carried loads, and walking speeds on trunk and lower-limb joint biomechanics. Design: Within-subjects repeated measures to determine the effects of different body armour types, carried loads, and walking speeds on trunk and lower-limb joint biomechanics. Methods: Twenty soldiers (29.5 ± 7.1yrs) completed a treadmill walking protocol in an unloaded (baseline) condition and wearing a control, Tiered Body Armour System (TBAS) and five different armour types (cARM1-2, pARM1) with two load configurations (15 and 30 kg) for a total of eight armour × load ensembles. In each ensemble, participants walked for 10 min at 1.53 m s −1 and 1.81 m s −1 speeds. Whole-body marker kinematics and ground reaction forces were used, along with a scaled anatomic model, to determine peak lower-limb joint angles, net joint moments, and negative knee work. Peak parameters were compared between armour types, walking speeds, and carried loads using repeated measures ANOVAs. Results: Peak plantarflexion and hip abduction moments were reduced when wearing cARM1 (p = 0.040, p = 0.045) and cARM2 (p = 0.045, p = 0.003) compared to TBAS, while carrying 30 kg and/or walking fast. This suggests positive benefits of load distribution at higher task demands. Joint moments increased when participants carried greater load and/or walked faster, and the combined effects of carried load and walking speed were mostly additive. Conclusions: Primarily hip-borne load carriage does not negatively alter joint kinetics, and some positive adaptations occurred during tasks with higher demands. These results can inform equipment design and physical training programs for load carriage.